Keanekaragaman Makanan, Kerawanan Pangan Rumah Tangga dan Stunting pada Anak di Kabupaten Bulukumba: Studi Cross-Sectional - Bohari, Nurul Hidayah; Dewi, Dewi; Erniawati, Erniawati; Riandhani Mulyoto, Raufina; Sumarmi, Sumarmi (Jurnal Keperawatan Muhammadiyah, 2025)
Background: Stunting remains a major public health problem in Indonesia, particularly in eastern regions such as Bulukumba District, South Sulawesi. Inadequate dietary diversity, household food insecurity, and suboptimal feeding practices are widely recognized as key contributors to chronic undernutrition among children under five years of age. Purpose: This study aimed to analyze the association between dietary diversity, household food insecurity, feeding practices, and stunting among children aged 0–59 months in Bulukumba District. Methods: A community-based cross-sectional study was conducted with total of 228 mother–child pairs were selected through two-stage cluster sampling. Child anthropometric measurements were collected to determine stunting status based on height-for-age z-scores. Dietary diversity was assessed using the Household Dietary Diversity Score (HDDS), while household food insecurity was measured using the Household Food Insecurity Access Scale (HFIAS). Data were analyzed using descriptive statistics and multivariable logistic regression. Results: The mean dietary diversity score indicated moderate food diversity. Most children had received exclusive breastfeeding and complementary feeding. However, logistic regression analysis showed that child sex, age, exclusive breastfeeding, and complementary feeding practices were not significantly associated with stunting (p > 0.05). Complementary feeding exhibited the highest odds ratio (OR = 2.01) but did not reach statistical significance. The regression model demonstrated good fit, although its explanatory power was low (Nagelkerke R² = 0.023). Conclusion: Stunting in Bulukumba is likely influenced by complex and multifactorial determinants. Strengthening dietary diversity, improving household food security, and promoting optimal feeding practices through integrated nutrition and social protection interventions are essential to reduce stunting prevalence.